Religious Character Education as a Strategy for Forming Religious Moderation in Students - Trismiwati Hulu; Daniel Solano Vargas (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to determine the implementation of religious character education in shaping students' religious moderation at SMK Negeri 3 Alasa. This study uses a qualitative descriptive approach with data collection techniques through observation and interviews with the principal, teachers, homeroom teachers, and students from grades X to XII. Religious character education is implemented through various activities such as the celebration of the beginning of the month service, prayer and reflection on the Holy Scriptures before and after learning, as well as student involvement in service activities in the church. In addition, during special months such as the celebration of ecclesiastical holidays such as Easter and Christmas. The results of the study show that these activities have a positive impact on student behavior, such as increasing tolerance, discipline, respect, solidarity, and concern for the environment. Religious character education has been proven to be an effective strategy in instilling the values ​​of religious moderation among students, especially in forming an attitude of mutual respect and living peacefully in diversity.